1994
DOI: 10.1002/tera.1420500209
|View full text |Cite
|
Sign up to set email alerts
|

Selenium kinetics, placental transfer, and neonatal exposure in cynomolgus macaques (Macaca fascicularis)

Abstract: Forty pregnant cynomolgus macaques were treated daily from gestational day 20 to 50 by nasogastric intubation of 0, 25, 150, or 300 micrograms selenium as L-selenomethionine/kg body weight. In each group, 7-8 pregnancies were terminated by hysterotomy at gestational day 100 +/- 2 and the fetuses were examined, while 2-3 pregnancies in each group were allowed to proceed to term. Selenium and soluble glutathione peroxidase were measured in: maternal, neonatal, and fetal plasma and erythrocytes; fetal kidney, liv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 47 publications
1
8
0
Order By: Relevance
“…This single case does not allow us to draw conclusions on the effects of high doses of selenium on the fetus. However, considering the high doses received and the absence of side effects on the fetus, we could hypothesize that the placenta can prevent an excessive transfer of selenium to the fetus, in agreement with animal data by Hawkes et al ().…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This single case does not allow us to draw conclusions on the effects of high doses of selenium on the fetus. However, considering the high doses received and the absence of side effects on the fetus, we could hypothesize that the placenta can prevent an excessive transfer of selenium to the fetus, in agreement with animal data by Hawkes et al ().…”
Section: Discussionsupporting
confidence: 91%
“…Animal experimental data are not conclusive: the selenium salts have been found to cross the placenta in hamsters (Willhite, Ferm, & Zeise, 1990) and rats (Bou-Resli, Mathew, Dashti, & Al-Zaid, 2002). However, in various animal species, including primates, the placenta seems to protect fetuses from selenium toxicity in case of maternal selenium poisoning (Hawkes et al, 1994). In mice, chronic exposure to selenium during pregnancy and lactation caused low birth weight and poor neonatal survival (Schroeder & Mitchener, 1971).…”
Section: Discussionmentioning
confidence: 99%
“…Se in fish fat can reach 59 % of the total amount found in muscle (Burger et al 1992). In mammals, experiments show that muscles of cynomologus macaques (Macaca fascicularis ) also have a higher concentration of Se than adipose tissue and a much higher capacity to retain supplemented Se (Hawkes et al 1994). In lactating women, urine Se is influenced by creatinine excretion and therefore by leanbody mass (Thomson et al 2001).…”
Section: Maternal Constitutional Factorsmentioning
confidence: 99%
“…Despite elevated selenium concentrations in fetal tissues, neonatal blood and milk, no deleterious effects on neonates were observed. The authors suggested, based on these results, that primate foetuses are well protected against selenium toxicity arising from high maternal L-selenomethionine intakes (Hawkes et al, 1994).…”
Section: Reproductive and Developmental Toxicitymentioning
confidence: 99%
“…In a study in pregnant female Macaques (Macaca fascicularis) administered Lselenomethionine (at a dose level providing 25, 150 and 300 µg selenium/kg bw/day) via nasogastric intubation during organogenesis, dose-dependent maternal toxicity as indicated by poor appetite and emesis was observed in the mid-and high-dose groups (Tarantal et al, 1991;Hawkes et al, 1994). The dose of 25 μg selenium/kg bw/day administered as Lselenomethionine was considered by the authors to produce no signs of selenium toxicity in the dams (a NOEL for maternal toxicity).…”
Section: Reproductive and Developmental Toxicitymentioning
confidence: 99%